Acetylation of citrate synthase inhibits Bombyx mori nucleopolyhedrovirus propagation by affecting energy metabolism. (December 2022) - Hu, Miao; Zhu, Yajie; Mo, Yuqian; Gao, Xu; Miao, Meng; Yu, Wei
Abstract: Many studies have confirmed that virus infection cause changes in the expression level and post-translational modifications of tricarboxylic acid cycle (TCA) enzymes. In a previous study, we found that the acetylation level of lysine 336 of Bombyx mori citrate synthase (BmCS) was remarkably unregulated after Bombyx mori nucleopolyhedrovirus (BmNPV) infection. In the present study, we found that BmN cells infected with BmNPV could up-regulate BmCS transient expression and promote the acetylation modification of BmCS. Transient expression vectors for over-expression of wild-type Bmcs and K336 acetylation mimic mutant (K336Q) were constructed to analyze enzyme activity, revealing that acetylation of K336 significantly reduced its activity. The obtained results indicated that BmCS knock-down or K336 acetylation similarly suppressed BmN cellular ATP production and mitochondrial membrane potential. Furthermore, the acetylation of K336 and the reduction of BmCS expression contributed to weakening the replication lever of the BmNPV proliferation and the generation of progeny viruses. In sum, our study on the single lysine 336 acetylation and knock-down of Bmcs revealed the potential mechanism for inhibiting the proliferation of BmNPV, which may provide novel insights for the development of antiviral strategies. Graphical abstract: Image 1 Highlights: BmN cells infected with BmNPV could up-regulate BmCS transient expression and promote the acetylation modification of BmCS. Knockdown and acetylation of BmCS reduce the activity of BmCS which downregulate the production of ATP and MMP. Knockdown and acetylation of BmCS contributed to inhibit the proliferation of BmNPV and the generation of progeny viruses.